Alcohol-induced changes in the serum of vascular endothelial growth factor and electrical inhomogeneity of the myocardium in young patients - P. V. Belogubov; V. I. Ruzov; V. V. Skvortsov; S. G. Trefilov; V. D. Shevchenko; E. I. Yegorov (Лечащий Врач, 2022)
The aim was to study alcohol-induced changes in the electrical inhomogeneity of the myocardium and the level of vascular endothelial growth factor in blood serum in young patients. 92 patients were examined. The first group consisted of 30 men and 30 women in a state of acute intoxication with subsequent examination of the withdrawal state in the clinic, the second group included 16 men and 16 women in a withdrawal state upon admission to the clinic. Age of patients in the first group: 36,00 (33,75-40,00) years (women) and 37,50 (33,75-41,25) years – men, age of patients of the second group: 36,00 (35,00-39,75) years (women) and 37,50 (34,25-39,75) years (men). The control group consisted of healthy individuals: 15 men aged 35,00 (29,00-39,00) years and 15 women aged 31,00 (28,00-40,00) years. The dispersion of the QTd interval was assessed using a high-resolution electrocardiography apparatus Poly-Spectrum 8/EX (Russia), in 12 standard leads, lasting 10 seconds. The concentration of ethanol in the blood was determined by an Agilent 6850 chromatograph (USA). Serum concentration of vascular endothelial growth factor was assessed using the Vector-Best reagent kit (Russia) on an enzyme immunoassay analyzer Hospitex diagnostics Plate Screen (Italy). Evaluation of the serum concentration of vascular endothelial growth factor in young alcohol-dependent patients showed an increase in its content, both in the acute and withdrawal periods, compared with patients in the control group. At the same time, there was a trend towards higher vascular endothelial growth factor values in men compared to women. It was found that the prehospital course of the withdrawal period is characterized by higher concentrations of serum vascular endothelial growth factor, compared with patients in whom the withdrawal period began in the clinic after acute alcohol intoxication. The hospital withdrawal period was accompanied by an increase in the value of the corrected dispersion of QTcd among women and men, compared with the acute period. Analysis of the incidence of violations of the processes of repolarization of the ventricular myocardium in the withdrawal period revealed its predominance in women compared to men. The development of a strategy for early prenosological diagnosis of myocardial arrhythmogenic activity, including the assessment of electrical inhomogeneity, made it possible to reveal the prevalence among young women of a more frequent occurrence of arrhythmogenic myocardial vulnerability in the withdrawal period of alcoholic excess compared to men. Alcohol-induced electrical inhomogeneity of the myocardium is accompanied by an increase in the serum concentration of vascular endothelial growth factor in young patients without overt cardiac pathology.